KEBIJAKAN PEMERINTAH TERHADAP PERLINDUNGAN HAK PEKERJA FREELANCE (HARIAN LEPAS) DI INDONESIA - Indriana, Ana (Investama : Jurnal Ekonomi dan Bisnis, 2021)
In the implementation of national development, manpower is one of the spearheads as a supporting element of the government which has a very important role for the success of development so that policies in the manpower sector in the national development program always strive to create as many job opportunities as possible in various business fields, balanced with an increase quality and increased protection of labor. The government and regulators in Indonesia always try to guarantee the rights of workers both from their citizens and foreign nationals who work in their countries. This is of course in line with the purpose of the formation of the State, namely to protect the entire Indonesian nation and all Indonesian bloodshed and to advance public welfare. However, the casual daily workforce working for companies today is experiencing a very dramatic situation. This is because there are no written contracts and regulations to guarantee legal protection and the safety and health of casual daily workers, and they tend to be run by the company. In its development, one form of legal protection for labor is regulated by the government, in Article 86 paragraph (1) letter a of Law Number 13 of 2003 concerning manpower it is explained that